Macular microvasculature alterations in patients with primary open-angle glaucoma: A cross-sectional study - Xu, Huan (Medicine (Baltimore), 2016)
To evaluate and compare macular microvasculature changes in eyes with primary open-angle glaucoma (POAG) to normal eyes, and to assess associations among the retinal microvasculature, neural structural damage, and visual field loss. Ninety-nine eyes (68 patients with POAG and 31 normal subjects) were enrolled in this study. Thirty-five eyes with early-stage glaucoma (EG), 33 eyes with advanced-stage glaucoma (AG), and 31 normal eyes were included. An optical coherence tomography system with a split-spectrum amplitude-decorrelation angiography algorithm was used to measure the macular capillary vessel area density and retinal thickness. Visual field testing (30-2 and 10-2 programs) was performed using a Humphrey field analyzer. Correlations between the capillary vessel area density, retinal thickness, and visual field parameters were analyzed. Compared to normal eyes, those with EG and AG had a lower macular capillary vessel area density and lesser retinal thickness (P < 0.001, all). Results of multivariate linear regression analyses showed that each standard deviation (SD) decrease in the vessel area density was associated with a 1.5% and 4.2% thinning of the full retinal thickness and inner retinal layer thickness, respectively. Each SD decrease in the vessel area density was also associated with a 12.9% decrease in the mean sensitivity and a 33.6% increase in the pattern standard deviation (P < 0.001, both). The Pearson partial regression analysis model showed that the vessel area density was most strongly associated with the inner retinal layer thickness and inferior hemimacular thickness. Furthermore, a lower vessel area density was strongly associated with a more severe hemimacular visual field defect and the corresponding hemimacular retinal thickness. The macular capillary vessel area density and retinal thickness were significantly lower in eyes with POAG than in normal eyes. A diminished macular microvasculature network is closely associated with visual field defects, which are dependent on structural damage due to POAG.